Light attenuation versus evolved carbon (AVEC) – A new way to look at elemental and organic carbon analysis. (February 2018) - Nicolosi, E.M.G.; Quincey, P.; Font, A.; Fuller, G.W.
Abstract: The Attenuation Versus Evolved Carbon (AVEC) plot is a new way to represent thermal-optical organic carbon/elemental carbon (OC/EC) analysis data. The accumulated carbon concentration is plotted against the attenuation (ln (I0 /I)). Unlike the thermogram, it provides information about the sample properties rather than the instantaneous instrument sensor status. The plot can be used to refine the determination of OC and EC split point, either from consideration of laser instability or transit time within the instrument; to investigate the optical properties of the particles; and to spot the early evolution of pyrolysed carbon (PC) and/or EC during the inert phase. 168 samples from three sites were studied. The gradient of the AVEC plot curve in the oxygenated phase provides information about the mass absorption cross section (σ) of the particles leaving the filter. The σ of the PC generated in the higher temperature Quartz protocol was greater than the PC generated in the lower temperature EUSAAR_2 protocol. Also, in both cases the PC evolved at a lower temperature in the oxygenated phase than the native EC. To minimise the shadowing effect, σ was also measured for the particles leaving the filter at the end of the analysis. These σ values, which are expected to be a combination of inherent σ together with fixed instrumental factors, were consistent between the different sites (45 ± 10 m 2  g −1 in rural samples, 42 ± 8 m 2  g −1 in urban samples and 35 ± 14 m 2  g −1 in roadside samples). The AVEC plot can be generated from the data routinely produced by the analytical instrument using the R-code supplied in the supplementary material. Graphical abstract: Image 1 Highlights: We provide a new way to represent thermal-optical OC/EC analysis data (AVEC plot). The AVEC plot focuses on the sample properties, not the instrument sensor status. It allows the investigation of the optical properies of carbon particles. The optical properties of pyrolysed ambient carbon differed between protocols.